BS EN IEC 62442-1. Energy performance of lamp controlgear. Part 1. Controlgear for fluorescent lamps. Method of measurement to determine the total input power of controlgear circuits and the efficiency of controlgear (16th October 2020) - British Standards Institution,
No abstract available